2004
DOI: 10.1007/s00027-004-0732-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus limitation of bacterial growth in high Arctic lakes and ponds

Abstract: Water from lakes and tundra ponds on Banks, Melville, Ellef-Ringnes, Ellesmere and Devon Island (74-79°N, 82-116°W) in the Canadian high Arctic was studied in batch culture experiments to test whether nitrogen, phosphorus or organic carbon limited bacterial growth and biomass accumulation. Water samples containing indigenous bacteria were amended with carbon (glucose), nitrogen (nitrate) or phosphorus (phosphate), either alone or in combination, and were incubated in the dark at ambient temperatures. Bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 47 publications
(53 reference statements)
4
32
0
Order By: Relevance
“…In aquatic systems, nutrient concentrations and ratios in the environment could limit C respiration when they deviate from the Redfield ratio (16 N: 1 P) or microbial N:P biomass ratios (7 N: 1 P; Cleveland & Liptzin 2007). Previous studies in Arctic aquatic ecosystems found bacterial production is usually limited by phosphorous (Granéli et al 2004;Hobbie & LaybournParry 2008), but we did not find a statistically significant positive relationship between extract C respiration potentials and PO 4 -P concentrations in our study. Our multiple linear regression analyses indicated positive correlation between C respiration and ammonium (NH 4 -N) concentrations in the soil extracts, suggesting potential N limitation in our system.…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic systems, nutrient concentrations and ratios in the environment could limit C respiration when they deviate from the Redfield ratio (16 N: 1 P) or microbial N:P biomass ratios (7 N: 1 P; Cleveland & Liptzin 2007). Previous studies in Arctic aquatic ecosystems found bacterial production is usually limited by phosphorous (Granéli et al 2004;Hobbie & LaybournParry 2008), but we did not find a statistically significant positive relationship between extract C respiration potentials and PO 4 -P concentrations in our study. Our multiple linear regression analyses indicated positive correlation between C respiration and ammonium (NH 4 -N) concentrations in the soil extracts, suggesting potential N limitation in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of DOC likely had an effect on bacterial community composition due to inputs of allochthonous higher-molecular weight compounds from the catchment area and associated different bacteria. The quantity of DOC is known to be among the most important factors controlling bacterial communities in lakes in both subarctic-arctic and temperate regions (Jansson et al 1996;Granéli et al 2004;Vrede 2005;Sawström et al 2007). In controlled enclosure experiments, DOC addition has had an immediate positive impact on bacteria abundance and production in an oligotrophic lake in northern Finland (Forsström et al unpublished data) and in a High-Arctic lake in Svalbard (Hessen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This change in water quality probably has an impact on bacterioplankton dynamics. Biomass of bacteria and their biological efficiency have been reported to be dependent on inorganic nutrients (Simon et al 1998;Granéli et al 2004), temperature (Ochs et al 1995;Rae and Vincent 1998), UV radiation (Laurion et al 1997) and grazing by nanoflagellates and cladocerans (Kankaala 1988;Laybourn-Parry and Marshall 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves that have not been conditioned by microbes are thought to be poor quality food for macroinvertebrate consumers, however, because of their physical and nutritional nature; microbes macerate leaves, producing a nitrogen and/or phosphorus-rich resource (Bärlocher and Kendrick 1975). The biomass and activity of aquatic microbes on leaves is often limited by nitrogen or phosphorus in the surrounding water (Suberkropp 1998b), and many studies have shown that nutrient addition facilitates growth of microbes in lakes, streams, and other aquatic systems (Elser et al 1995, Stelzer et al 2003, Granéli et al 2004. Such facilitation of microbe growth can also have indirect positive eVects on detritivores (Rosemond et al 2001).…”
Section: Introductionmentioning
confidence: 98%